The submandibular and sublingual glands maintain oral microbial homeostasis through multiple antimicrobial proteins - Li, Yanan; Liu, Jingming; Guan, Tong; Zhang, Yuxin; Cheng, Qianyu; Liu, Huikai; Liu, Chang; Luo, Wenping; Chen, Hong; Chen, Liang; Zhao, Tianyu (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Oral microbial homeostasis is a key factor affecting oral health, and saliva plays a significant role in maintaining oral microbial homeostasis. The submandibular gland (SMG) and sublingual gland (SLG) together produce the most saliva at rest. Organic ingredients, including antimicrobial proteins, are rich and distinctive and depend on the type of acinar cells in the SMG and SLG. However, the functions of the SMG and SLG in maintaining oral microbial homeostasis have been difficult to identify and distinguish, given their unique anatomical structures Methods In this study, we independently removed either the SMG or SLG from mouse models. SMGs were aseptically removed in three mice in the SMG-removal group, and SLGs were aseptically removed in three mice in the SLG-removal group. Three mice from the sham-operated group were only anesthetized and incised the skin. After one month, we analyzed their oral microbiome through 16S rRNA sequencing. And then, we analyzed each gland using proteomics and single-cell RNA sequencing. Results Our study revealed that the microbiome balance was significantly disturbed, with decreased bacterial richness, diversity, and uniformity in the groups with the SMG or SLG removed compared with the sham-operated group. We identified eight secreted proteins in the SMG and two in the SLG that could be involved in maintaining oral microbial homeostasis. Finally, we identified multiple types of cells in the SMG and SLG (including serous acinar, mucinous acinar, ductal epithelial, mesenchymal, and immune cells) that express potential microbiota homeostasis regulatory proteins. Our results suggest that both the SMG and SLG play crucial roles in maintaining oral microbial homeostasis via excretion. Furthermore, the contribution of the SMG in maintaining oral microbial homeostasis appears to be superior to that of the SLG. These findings also revealed the possible antimicrobial function of gland secreta. Discussion Our results suggest that control of oral microbial dysbiosis is necessary when the secretory function of the SMG or SLG is impaired. Our study could be the basis for further research on the prevention of oral diseases caused by microbial dysbiosis.